Inflammation‐induced mammalian target of rapamycin signaling is essential for retina regeneration. Issue 1 (24th August 2019) - Zhang, Zhiqiang; Hou, Haitao; Yu, Shuguang; Zhou, Cuiping; Zhang, Xiaoli; Li, Na; Zhang, Shuqiang; Song, Kaida; Lu, Ying; Liu, Dong; Lu, Hong; Xu, Hui
Abstract: Upon retina injury, Müller glia in the zebrafish retina respond by generating multipotent progenitors to repair the retina. However, the complete mechanisms underlying retina regeneration remain elusive. Here we report inflammation‐induced mammalian target of rapamycin (mTOR) signaling in the Müller glia is essential for retina regeneration in adult zebrafish. We show after a stab injury, mTOR is rapidly activated in Müller glia and later Müller glia‐derived progenitor cells (MGPCs). Importantly, mTOR is required for Müller glia dedifferentiation, as well as the proliferation of Müller glia and MGPCs. Interestingly, transient mTOR inhibition by rapamycin only reversibly suppresses MGPC proliferation, while its longer suppression by knocking down Raptor significantly inhibits the regeneration of retinal neurons. We further show mTOR promotes retina regeneration by regulating the mRNA expression of key reprogramming factors ascl1a and lin‐28a, cell cycle‐related genes and critical cytokines. Surprisingly, we identify microglia/macrophage‐mediated inflammation as an important upstream regulator of mTOR in the Müller glia and it promotes retina regeneration through mTOR. Our study not only demonstrates the important functions of mTOR but also reveals an interesting link between inflammation and the mTOR signaling during retina regeneration. Main Points: mTOR is essential for Müller glia reprogramming and proliferation, as well as the regeneration of retinal neurons in zebrafish retina. Microglia/macrophage‐mediated inflammation promotes retina regeneration through mTOR.